2017
DOI: 10.1002/2017gc006868
|View full text |Cite
|
Sign up to set email alerts
|

The Gondou hydrothermal field in the Ryukyu Arc: A huge hydrothermal system on the flank of a caldera volcano

Abstract: High‐resolution geophysical mapping was conducted from an autonomous underwater vehicle on the flank of Daisan‐Kume Knoll in the Ryukyu Arc, southwest of Japan. 1 m resolution bathymetry identified 264 spires, 173 large mounds and 268 small mounds within a depression that is up to 1600 m wide and up to 60 m deep, at water depths between 1330 and 1470 m. Hydrothermal venting is strongly inferred from the observation of plumes in sidescan sonar imagery and positive temperature anomalies over the spires and mound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 47 publications
(69 reference statements)
1
15
0
Order By: Relevance
“…The slope at the northern margin of the southern OT shows a steeper gradient than that in the northern OT and is cut by submarine channels of varying size. Over ten hydrothermal vents have been found through the OT, and some of them have been investigated in great detail (e.g., Beaulieu 2015;Ishibashi et al 2015;Minami and Ohara 2017). However, a volcanic front is recognizable only to the west of the Ryukyu Arc in the northern and middle OT, but not in the southern OT.…”
Section: Introductionmentioning
confidence: 99%
“…The slope at the northern margin of the southern OT shows a steeper gradient than that in the northern OT and is cut by submarine channels of varying size. Over ten hydrothermal vents have been found through the OT, and some of them have been investigated in great detail (e.g., Beaulieu 2015;Ishibashi et al 2015;Minami and Ohara 2017). However, a volcanic front is recognizable only to the west of the Ryukyu Arc in the northern and middle OT, but not in the southern OT.…”
Section: Introductionmentioning
confidence: 99%
“…This site is located in the western offshore of Kumejima Island, which is approximately 100 km west of Okinawa Main Island. In 2014, the Japan Coast Guard conducted acoustic bathymetric surveys using the cruising AUV Gondou at altitudes of 50–70 m and confirmed that myriads of chimneys and mounds exist (Minami and Ohara, ). In 2015 and 2016, the Japan Agency for Marine‐Earth Science and Technology also conducted surveys using the cruising AUV Urashima (Kitada et al, ; Nakamura, ) and the HOV Shinkai 6500 (Kasaya, ), respectively.…”
Section: Deployment In An Active Hydrothermal Vent Fieldmentioning
confidence: 97%
“…Chimney structures are typically formed in the seafloor of hydrothermal vent fields and can grow to a height of several tens of meters (Nozaki et al, ; Minami and Ohara, ; Tivey, ). To avoid collision with these structures, Hobalin has an obstacle avoidance system consisting of several devices such as forward‐ and downward‐looking cameras, line lasers, and thermometers (Okamoto, Tamura, et al, ; Okamoto et al, ).…”
Section: Hovering‐type Auv Hobalinmentioning
confidence: 99%
“…Hydrothermal activities usually occur along with submarine edifices (e.g., volcanos, mounds and chimneys) and are rich in mineral deposits, reflecting subsurface and active hydrothermal circulation. The formation and evolution of hydrothermal fields are regionally controlled by tectonics such as plate subduction and associated rifting, and are locally controlled by magma activities, host rocks composition, segregation process as well as fluid migration (Von Damm 1990;Charlou et al 1996;Tivey 2007;Kelley et al 2012;Minami and Ohara 2017). For last decade, the potential of marine mineral resources in hydrothermal fields enriched by hydrothermal circulation that expedite chemical exchanges between hydrothermal fluid and its surrounding crust is receiving increasing attention, especially in the Okinawa Trough (e.g., Inagaki et al 2006;Ishibashi et al 2015;Nozaki et al 2016;Toki et al 2016;Minami and Ohara 2017), which is a back-arc basin at rear side of the Ryukyu arctrench system along the tectonic boundary between the Eurasian Plate and subducting Philippine Sea Plate (Lee et al 1980;Letouzey and Kimura 1986;Sibuet et al 1987Sibuet et al , 1998.…”
Section: Introductionmentioning
confidence: 99%